Cover Picture: Plasma Process. Polym. 3∕2014. Issue 3 (March 2014) - Dolci, Luisa Stella; Quiroga, Santiago David; Gherardi, Matteo; Laurita, Romolo; Liguori, Anna; Sanibondi, Paolo; Fiorani, Andrea; Calzà, Laura; Colombo, Vittorio; Focarete, Maria Letizia
<x xml:space="preserve">Abstract</x> Front Cover: Non‐thermal atmospheric pressure plasma allowed surface properties modification of electrospun poly(L‐lactic acid) scaffold. Mouse embryonic fibroblast cells cultured on treated scaffolds showed a more elongated and "dendritic" morphology than cells cultured on the untreated ones. Further details can be found in the article by Maria Letizia Focarete et. al. on page 203. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>